A Schedule Optimization Model on Multirunway Based on Ant Colony Algorithm. (28th September 2014) - Jiang, Yu; Xu, Zhaolong; Xu, Xinxing; Liao, Zhihua; Luo, Yuxiao
Abstract : In order to make full use of the slot of runway, reduce flight delay, and ensure fairness among airlines, a schedule optimization model for arrival-departure flights is established in the paper. The total delay cost and fairness among airlines are two objective functions. The ant colony algorithm is adopted to solve this problem and the result is more efficient and reasonable when compared with FCFS (first come first served) strategy. Optimization results show that the flight delay and fair deviation are decreased by 42.22% and 38.64%, respectively. Therefore, the optimization model makes great significance in reducing flight delay and improving the fairness among all airlines.